(untitled) (Journal of Tropical Pharmacy and Chemistry, 2021)
Caffeine has wide therapeutic uses, is widely used in the pharmaceutical field as an analgesic, and reduces fever. Caffeine is also widely added as a flavoring agent in soft drinks such as coca cola and energy drinks. Excess caffeine consumption or in the long term can have negative effects on health. The caffeine content in drinks varies by brand, from 10 to 50 mg per serving. This study aims to determine the amount of caffeine in carbonated drinks and energy drinks using chloroform solvent extraction techniques and activated carbon adsorption techniques. The amount of caffeine in the drink was analyzed by a spectrophotometric method using the maximum wavelength. The results showed that the amount of caffeine with the extraction technique in coca cola drinks was (31.39 ± 0.528 mg/serving), pepsi blue (27.93 ± 0.159 mg/serving), red bull (39.79 ± 0.233 mg/serving), and panther (43.37 ± 0.860 mg/serving). The adsorption technique obtained in coca cola drinks are (32.07 ± 0.164 mg/serving), pepsi blue (27.42 ± 0.174 mg/serving), red bull (31.35 ± 0.132 mg/serving), and panther (33.83 ± 0.205 mg/serving). In the coca cola drink, the best results are obtained close to the actual value as stated on the label. Meanwhile, for the three other types of drinks, the amount of caffeine obtained was lower than expected, and still below the maximum allowable limit. Of the two techniques investigated, the extraction technique still gave better results than the adsorption technique.